2017
DOI: 10.1007/s40520-016-0719-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the turning characteristics according to the severity of Parkinson disease during the timed up and go test

Abstract: Patients with PD exhibited significant differences in all variables of interest compared to the controls. The step length and foot clearance height as well as the TUG test during the turning phase may be helpful for measuring turning in patients with different severity levels of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Turning difficulty is common among people with PD in advanced stages. People with PD turn slowly with prominent small steps, even demonstrating gait disturbances such as freezing of gait (20)(21)(22)(23). But our study has shown that there is a problem of turning in mild to moderate Parkinson's disease.…”
Section: Discussionmentioning
confidence: 56%
“…Turning difficulty is common among people with PD in advanced stages. People with PD turn slowly with prominent small steps, even demonstrating gait disturbances such as freezing of gait (20)(21)(22)(23). But our study has shown that there is a problem of turning in mild to moderate Parkinson's disease.…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, there was no relationship between ALFF values in right lingual gyrus and TUG test time or PIGD scores in the PD‐GG group. TUG test can be used to evaluate the walking or turning characteristics and predict fall risks in PD . Besides, PIGD scores from UPDRS‐III scores can also reflect gait or balance function in PD patients to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Lingual gyrus, located in occipital cortex (also known as visual association cortex), participated in spatial orientation 39 and visuospatial information processing. 40,41 Moreover, changes in the flow of visual information mainly dominated by right hemisphere, 42,43 had an influence on balance disorders 44 48 and predict fall risks in PD. 49,50 Besides, PIGD scores from UPDRS-III scores can also reflect gait or balance function in PD patients to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…People with PD turn slowly with prominent small steps, even demonstrating gait disturbances such as freezing of gait. [20][21][22][23] But study has shown that there is a problem of turning in mild to moderate Parkinson's disease. It also showed that in these patients, the ability to turn was associated with age, duration of illness, UPDRS, FIM, Tinetti walking-balance, the Berg balance, 6m walking time, and the number of steps taken.…”
Section: Discussionmentioning
confidence: 99%